Endobronchial Aspergillosis Presenting as an Isolated Airway Lesion in an Immunocompromised Patient - Mohsen Sadeghi; Fatemeh Sadat Hosseini Khajouei; Haniyeh GhanbarAliAkhavan; Amir Morteza Soleimani (Respirology Case Reports, 2026)
ABSTRACT Endobronchial aspergillosis (EBA) is an uncommon manifestation of Aspergillus airway disease characterized by fungal involvement of the tracheobronchial lumen. It may present with non‐specific respiratory symptoms, including dyspnea, cough and hemoptysis, and can mimic endoluminal airway tumours. Predisposing factors include immunosuppressive conditions such as corticosteroid therapy, malignancy, chemotherapy and neutropenia. Definitive diagnosis relies on bronchoscopic evaluation with histopathological confirmation. Due to its rarity, evidence regarding optimal management remains limited. This case emphasizes that isolated airway Aspergillus infection may occur without parenchymal lung involvement and may be associated with a rapidly fatal clinical course despite prompt antifungal therapy.